If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying squarex + -4 = 0 Reorder the terms: -4 + aeqrsux = 0 Solving -4 + aeqrsux = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + aeqrsux = 0 + 4 Combine like terms: -4 + 4 = 0 0 + aeqrsux = 0 + 4 aeqrsux = 0 + 4 Combine like terms: 0 + 4 = 4 aeqrsux = 4 Divide each side by 'eqrsux'. a = 4e-1q-1r-1s-1u-1x-1 Simplifying a = 4e-1q-1r-1s-1u-1x-1
| x^5y^5-x^4y^3+x^3y^2+x^2y^2=0 | | 3(x-5)=15(x-1) | | 7(m+9)=112 | | 2(4v-v)=4(6-v) | | 12x+7=15x-8 | | 8x-(2+3x)= | | 4(-5c+8d-8)= | | 13-20g=53 | | 5x+4=3-4 | | (3x-6)=12 | | 4a^2=5a | | Sinx=.52 | | n-8+13= | | 7-12+17-20= | | .013-.02g=.053 | | (3i)(x)=y | | (30+3n)-(20+2n)= | | 9x-97+18x-104+90+x+19=119 | | x(x+1)=16-8 | | -7x=-8-3x-8 | | 2(m-3)=2+3m | | (7x+4)(5x+8)=144 | | f(x+7)=x^2+3x+6 | | 9x-97+18x-104+90=119 | | -9y-2=-8y-5 | | 4(2x-7)-2(x+8)=12x-42 | | 2x+7=0.5(5x-4) | | 8.1x+11.25=-11.9+10.03 | | -8x-9=8x | | 5(-3x-6)=-90 | | 4[8-(-4x-3)]=96x+104 | | 4[8-(-4x-3)]=96x+104 |